2016
DOI: 10.18869/acadpub.3dj.5.2.17
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Dental Development and Cervical Vertebrae Development Assessed Using Radiography in an Iranian Population

Abstract: Introduction:Determining the skeletal age and remaining growth potential of patients are important factors in orthodontic treatment. Evaluating cervical vertebrae development is a reliable method for determining skeletal age. This study aimed to evaluate the correlation between dental calcification and stages of skeletal maturation. Materials and methods:This descriptive cross-sectional study was conducted on 84 panoramic radiographs and lateral cephalometrics related to 10-15-year-old patients without systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Also, dental calcification is considered to follow an independent process that is less affected by dental arch space, 15 deciduous teeth extraction, and dental eruption . In addition, to reduce radiation exposure when evaluating skeletal maturity, researchers have attempted to correlate dental calcification stages with cervical vertebrae and hand-wrist bone maturation stages among different [16][17][18] populations . Chertkow had earlier suggested using lower canines to predict pubertal growth spurt due to the high level of correlation with the hand and wrist bones 19 ossification stages .…”
Section: Introductionmentioning
confidence: 99%
“…Also, dental calcification is considered to follow an independent process that is less affected by dental arch space, 15 deciduous teeth extraction, and dental eruption . In addition, to reduce radiation exposure when evaluating skeletal maturity, researchers have attempted to correlate dental calcification stages with cervical vertebrae and hand-wrist bone maturation stages among different [16][17][18] populations . Chertkow had earlier suggested using lower canines to predict pubertal growth spurt due to the high level of correlation with the hand and wrist bones 19 ossification stages .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown a strong correlation between calcification stages of various mandibular teeth particularly the mandibular canine and the skeletal maturity [30][31][32][33][34][35][36][37][38][39][40][41][42][43] , while others have refuted this claim [44][45][46][47][48] . Because of this controversy and the well-established racial variation in the stages of dental calcification 30,33,42,[49][50][51] , the present study was undertaken to investigate the reliability of mandibular canine maturation stages in predicting pubertal growth spurt in a sample of Egyptian orthodontic patients.…”
Section: Introductionmentioning
confidence: 99%